Effect of Atmospheric Pressure Plasma Treatment on Seed Decontamination and Sprouting of Pak Choi (Brassica rapa L. subsp. chinensis (L.) Hanelt) - Pradeep Puligundla (Science Faculty of Chiang Mai University, 2019)
The application of non-thermal plasmas, as a substitute to chemical pre-germination treatments, for seed disinfection is increasingly becoming common in recent years. In this study, the potentiality of corona discharge plasma jet (CDPJ) for microbial inactivation in pak choi sprout seeds was evaluated, including the CDPJ exposure effects on the seed germination and physico-chemical properties of sprouts grown from the CDPJ-treated seeds. Aerobic bacteria, B. cereus, E. coli, Salmonella spp. and molds and yeasts were detected as contaminants in the seeds. All the detected microorganisms of the seeds were reduced in the range of 1.3-2.1 log CFU/g on treatment using the CDPJ for 3 min. The microbial inactivation patterns were better explained by pseudo-first-order kinetics. The CDPJ seed treatment for up to 2 min was found to have beneficial effects on seed germination rate and growth of seedlings. Sprouts grown from the CDPJ-treated seeds exhibited no significant changes in the levels of moisture (mean range 84.76-87.18 %), reducing sugars (0.776-0.796 %), total phenolic content (5.69-5.95 mg GAL/g) and DPPH radical scavenging activity (62.63-64.78 %) compared to untreated controls. Sensory characteristics of pak choi sprouts grown from the plasma-treated (up to 2 min) seeds were not significantly different from controls.